The effect of extrinsic factors on simulated 20-km time trial performance - Peveler, W. W.; Green, M. (The Journal of Strength and Conditioning Research, 2010)
During time trials cyclists start individually with a uniform time gap between riders. With the exception of the first and last cyclists all riders will chase riders ahead and be chased from behind. The purpose of this study was to determine if cycling in a lead or chase position would influence 20-km time trial performance. Eight male cyclists performed four 20-km indoor time trials. During trial 1 (T1) individuals cycled as fast as possible. Prior to the start of trial 2 (T2) subjects were shown times and rank order from T1 and attempted to improve rank among opponents. After T2 subjects were ranked again and paired with the closest competitor. Subjects were alternately positioned to lead (TL) and chase (TC) in trials 3 and 4. TL and TC were counterbalanced. Means for time, mean power (MP), ratings of perceived exertion (RPE), and heart rate (HR) were recorded and pacing evenness was compared between trials using deviation scores (power variation at designated distances from overall mean). Repeated-measures analysis of variance (ANOVA) (alpha = 0.05) indicated no significant differences for HR or RPE. For time, T2 (33.84 ± 1.38 minutes) was significantly faster than T1 (34.80 ± 2.25 minutes) and MP was significantly greater (T1 = 229 ± 36 W, T2 = 243 ± 24 W). Time for TC (33.52 ± 1.33 minutes) was significantly faster than T1 (34.80 ± 2.25 minutes). Pacing during TC (9 ± 3 W) was significantly more even in comparison to TL (12 ± 1 W). No significant difference in performance was detected between TC and TL. In conclusion, extrinsic factors (chase vs. lead position) did not affect overall performance, even when pacing altered between trials; however, differences in performance times may represent meaningful differences in competitive settings.